Compact objects in close orbits as gravitational wave sources: Formation scenarios and properties - Zhenwei Li; Xuefei Chen (Results in Physics, 2024)
Gravitational Waves (GWs) provide a unique way to explore our Universe. The ongoing ground-based detectors, e.g., LIGO, Virgo, and KAGRA, and the upcoming next-generation detectors, e.g., Cosmic Explorer and Einstein Telescope, as well as the future space-borne GW antennas, e.g., LISA, TianQin, and TaiJi, cover a wide range of GW frequencies from ∼10−4Hz to ∼103Hz and almost all types of compact objects in close orbits serve as the potential target sources for these GW detectors. The synergistic multi-band GW and EM observations would allow us to study fundamental physics from stars to cosmology. The formation of stellar GW sources has been extensively explored in recent years, and progress on physical processes in binary interaction has been made as well. Furthermore, some studies have shown that the progress in binary evolution may significantly affect the properties of the stellar GW sources. In this article, we review the formation channels of compact objects in close orbits and discuss their implications for GW observations.